EARLY DETECTION OF HYPERTENSION IN ELDERLY AND IMPROVING THE QUALITY OF LIFE THROUGH HEALTHY LIFE BEHAVIOR - Siregar, Fazidah Aguslina (Journal of Saintech Transfer, 2019)
Hypertension is common in the elderly. The diseases is related to unhealthy lifestyles include unhealthy food habitual and lack of physical activity. Delay in detecting and handling have an impact on the quality of life. The community service had been carried out at Tanjung Anom Village, Pancurbatu subdistrict, Deli Serdang. The purpose of this activity to detect hypertension through health examination (Height, weight, waist size, blood pressure, blood sugar levels, cholesterol, and uric acid level), followed by education on healthy lifestyles and elderly gymnastic exercise and preparation of healthy menu. Of the 49 elderly were present, 26 people (53.1%) were obese, 12 people (24.5%) had diastolic hypertension, and 30 people (61.2%) were at the stage of prehypertension. Based on risk factors, 7 people (14.3%) had high blood glucose levels, as many as 38 people (77.6%) had high cholesterol levels and 28 people (57.1%) with high uric acid levels. From the results, most of elderly have high blood pressure. In the effort to reduce the number of hypertensive patients in the elderly, it is necessary to early detection and applied a healthy lifestyle.